Financial Distress Analysis: Cigarette Companies on Idx, Pandemic & Excise Tax Impact (2019-2023) - Lutfan, Ifan Muhamad; Wati, Lela Nurlela; Arifin, Agus Zainul (Politeknik Siber Cerdika Internasional, 2025)
This study aims to analyze the condition of financial distress in cigarette companies listed on the Indonesia Stock Exchange during the period 2019 to 2023, as well as identify the influence of external factors in the form of an increase in excise rates and the COVID-19 pandemic on the level of distress risk. The problem of financial distress is a crucial issue because the cigarette industry faces pressure from the perspective of fiscal regulations and the global health crisis that has an impact on the company's financial performance. This research method is quantitative with a descriptive and associative approach. The research sample consisted of four cigarette companies, namely PT HM Sampoerna Tbk (HMSP), PT Gudang Garam Tbk (GGRM), PT Wismilak Inti Makmur Tbk (WIIM), and PT Bentoel Internasional Investama Tbk (RMBA). The data used are secondary data in the form of annual financial statements, percentage increase in excise rates, and COVID-19 pandemic status as dummy variables. To measure financial distress, three predictive models are commonly used in the literature, namely: Altman Z-Score, Springate S-Score, and Zmijewski X-Score. Furthermore, a simple regression analysis was carried out to determine the influence of excise rates and the pandemic on distress scores. The results showed that HMSP and WIIM were consistently in a healthy financial condition according to all three models, while GGRM was volatile but relatively stable. In contrast, the RMBA shows a score that indicates a distressed condition almost every year. The Zmijewski model was shown to be the most sensitive in detecting distress compared to the other two models. Regression analysis revealed that the increase in excise rates and the COVID-19 pandemic had a significant effect on distress scores with negative directions in the Altman and Springate models, as well as positive directions (increased risks) in the Zmijewski model. The study concludes that external factors have a significant contribution to the risk of bankruptcy of cigarette companies, and it is important for company management, investors, and regulators to consider these factors in strategic decision-making. Predictive models can be used as an early detection tool against declining corporate financial health